Giant Cell Tumor Arising from Fibular Head in Immature Skeleton Treated with Marginal Excision - Pandey, Suresh (Journal of College of Medical Sciences-Nepal, 2018)
ABSTRACT Giant Cell tumor (GCT) is the benign tumor commonly found in second to fourth decade of life. Proximal fibula is very rare site and its occurrence in immature skeleton is still rare with very limited case report. We present a case of painful bony lesion arising from proximal fibula diagnosed as GCT in 15 year boy which was managed successfully with marginal excision and lateral collateral ligament anchorage in proximal tibia. There is no evidence of local recurrence, lung metastasis, knee pain and instability till 24 months of follow up. Keywords: giant cell tumor; proximal fibula; marginal excision .